Lung cancer screening in never-smokers: facts and remaining issues. Issue 5 (12th November 2020) - Infante, Maurizio V.; Cardillo, Giuseppe
The final publication of the NELSON trial data [1 ] has corroborated the findings of the National Lung Screening Trial (NLST) confirming the ability of lung cancer screening with low-dose computed tomography (LDCT) to detect lung cancer at an early stage and significantly reduce lung cancer mortality in high-risk groups [2 ]. A similar probability of unwanted harm is to be expected in both ever- and never-smokers undergoing CT screening, together with a slightly lower lung cancer detection rate in the latter https://bit.ly/3izc1ZW